Modelling and simulation based assessment in sustainable bioprocess development - De Beer, Adrian (Centre for Bioprocess Engineering Research, 2014)
Modelling and simulation enhance our insight and understanding of chemical processes and aid in identifying bottlenecks and potential improvements. A simplified simulation package, providing a reasonable estimate of material and energy usage and process emissions is often valuable in very early stages of process development, when temporal and financial limitations do not allow for more detailed estimates. Environmental burdens are an increasing concern in industrial processes and various methodologies and tools have been developed for gathering and analysis of process information to enhance understanding of the process system and inform decision makers. The systems nature of these approaches is aimed at mitigation of environmental burdens through improved technologies, sustainable resource consumption and screening of process alternatives. Ideally, the process design team should bring together these tools in early stages of development when design flexibility is greatest. In the present study, such a simplified approach to bioprocess design is demonstrated using a case study for the large-scale production of citric acid.